The effect of a new feed additive of humic nature on morphometric indicators of laboratory rats depending on the dose - Chumak, Vladislav; Chumak, V.; Chumak, V. O.; Chumak, V. A.; Чумак, Владислав Олександрович; Garashuk, M. I.; Garashchuk, M.; Harashchuk, M. I.; Garashuk, Marina; Garaschuk, M. I.; Гаращук, Марина Іванівна; Galuzina, Liudmyla; et al. (Dnipro State Agrarian and Economic University, 2022)
The study of the effects of natural biologically active substances, manifestations and consequences of their application to different species of animals or under different conditions is being conducted. Peculiarities of the implementation of such effects when used separately or in combination, in particular, humic acids with mineral or organic acids, creates opportunities for optimal combination or solution to the complexities of the technological setting of feed additives. Changes in the morphometric parameters of internal organs in rats under the influence of the new feed additive of humic nature «Animal Forte» were detected. The established biochemical changes are confirmed at the histological level. In terms of the degree of expressiveness of the protective effect on the state of the liver parenchyma of rats, the dilution exceeds this dilution. No structural changes were detected in micropreparations of kidneys in animals of groups 2, 3, and 4, full blood and stasis in the capillaries of vascular glomeruli were observed. In the control and fifth experimental groups, the presence of damaged tubules, in which the brush border is rejected, was noted during the examination of kidney histopreparations. The morphometric parameters of the liver underwent the most pronounced changes in animals 1 and 2, intestines - 1 and 4, and kidneys and hearts - 2 and 5 of experimental groups, respectively. A smaller liver mass was found in the animals of the experimental groups, in particular, a decrease in the liver index in rats of the 1st and 2nd experimental groups by 21 % and 15 %, respectively. Kidneys in animals of experimental groups 2 and 5 had 14 % less weight, but the kidney index did not have significant changes in rats of all experimental groups compared to the control. Almost similar changes were related to heart weight, animals of experimental groups 2 and 3 also had probable changes by 13 %, and 5 groups by 14 %. Intestinal mass was significantly smaller in animals 1 (by 14 %), 3 (by 10 %) and 4 (by 11 %) of experimental groups, but the index was reduced only in animals of experimental group 1 by 16 %. Проводиться вивчення ефектів природних біологічно активних речовин, прояви та наслідки застосування різним видам тварин або за неоднакових умов. Особливості реалізації таких ефектів при окремому або комбінованому використанні, зокрема гумінових кислот із мінеральними або органічними кислотами, створює можливості оптимального поєднання або вирішення складнощів технологічного задавання кормових добавок. Виявляли зміни морфометричних показників внутрішніх органів у щурів за впливу нової кормової добавки гумінової природи «Animal Forte». Встановлені біохімічні зміни підтверджуються на гістологічному рівні. За ступенем вираженості протекторної дії на стан печінкової паренхіми щурів розведення перевищує таке розведення. Структурних змін щодо мікропрепаратів нирок у тварин 2, 3 і 4 груп не виявлено, спостерігаються повнокров’я та стази в капілярах судинних клубочків. У контрольній та п’ятій дослідній групах при дослідженні гістопрепаратів нирок відзначали наявність пошкоджених канальців, у яких відбувається відторгнення щіткової облямівки. Найбільш виразних змін морфометричні показники печінки зазнали у тварин 1 і 2, кишечника – 1 і 4, а нирок і серця - 2 і 5 дослідних груп відповідно. Виявлено меншу масу печінки у тварин дослідних груп, зокрема зниження індексу печінки у щурів 1 і 2 дослідних група на 21% та 15% відповідно. Меншу маси на 14% мали нирки у тварин 2 та 5 дослідних груп, проте індекс нирок не мав суттєвих змін у щурів усіх дослідних груп проти контролю. Майже аналогічні зміни стосувались маси серця, вірогідні зміни мали також тварини 2 і 3 дослідних груп на 13%, а 5 групи на 14%. Маса кишечника було вірогідно меншою у тварин 1 (на 14%), 3 (на 10%) і 4 (на 11%) дослідних груп, але індекс виявився зниженим лише у тварин 1 дослідної групи на 16%.
Вплив нової кормової добавки гумінової природи на морфометричні показники лабораторних щурів залежно від дози
Чумак Владислав Олександрович https://orcid.org/0000-0002-0140-3982 Гаращук Марина Іванівна https://orcid.org/0000-0003-1533-6490 Галузіна Людмила Ігорівна http://orcid.org/0000-0003-0478-0027
Keywords: morphometric parameters; морфометричні показники; «Animal Forte»; «Animal Forte»; laboratory rats; лабораторні щури